2019
DOI: 10.1007/s10901-019-09678-8
|View full text |Cite
|
Sign up to set email alerts
|

Changing patterns in residential preferences for urban or suburban living of city dwellers

Abstract: Many cities in the western world have recovered from the urban crisis after the industrialization period and have become attractive places to live and work. It seems obvious to conclude that the preference for urban living has increased. But is this really the case? The (increased) preference for urban living may also be driven by demographic, socioeconomic and socio-cultural changes in the population rather than by a structural change in residential preferences. In depth analysis of the stated residential pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 52 publications
1
18
0
1
Order By: Relevance
“…Because it has become increasingly difficult for young adults to pursue a linear housing career in cities like Amsterdam (Hochstenbach & Boterman, 2015), flexible life arrangements have expanded in Dutch cities (Hochstenbach, Wind, & Arundel, 2020). Although young professionals are usually expected to value urban living (Fincher & Costello, 2005;Muhammad et al, 2007), young singles show no intention to settle long term in Amsterdam (Booi & Boterman, 2019). This is consistent with the introduction of short-term, flexible tenure forms in the shared housing market.…”
Section: Students and Young Professionals Shifting From 'Generation mentioning
confidence: 80%
See 1 more Smart Citation
“…Because it has become increasingly difficult for young adults to pursue a linear housing career in cities like Amsterdam (Hochstenbach & Boterman, 2015), flexible life arrangements have expanded in Dutch cities (Hochstenbach, Wind, & Arundel, 2020). Although young professionals are usually expected to value urban living (Fincher & Costello, 2005;Muhammad et al, 2007), young singles show no intention to settle long term in Amsterdam (Booi & Boterman, 2019). This is consistent with the introduction of short-term, flexible tenure forms in the shared housing market.…”
Section: Students and Young Professionals Shifting From 'Generation mentioning
confidence: 80%
“…Having moved to cities to complete higher education, young singles tend to stay for the first years of their careers (Booi & Boterman, 2019). Amsterdam concentrates this fast-growing group (ibid), with one-person households representing half of the population, and one-third of all households being aged 20 to 34 (Onderzoek Informatie en Statistiek [OIS], 2017).…”
Section: Students and Young Professionals Shifting From 'Generation mentioning
confidence: 99%
“…As a part of the urban resurgence (Turok & Mykhnenko, 2007, 2008) or reurbanisation trend (Kabisch & Haase, 2011), the number of families with children is on the rise again in several European cities (Booi & Boterman, 2020; Lilius, 2014). Although several studies have suggested that cities have become more popular environments in which to raise children, empirical data on actual residential mobility in the Netherlands indicate that the birth of a first child is still a turning point in the life course (Stone et al, 2014) that triggers couples to leave the city.…”
Section: Discussionmentioning
confidence: 99%
“…However, the traditional link between family formation and suburbanization seems to be fading. During the first decades of the 21st century, the number of families with children has once again been on the rise in many European cities (Booi & Boterman, 2020;Buzar et al, 2007;Lilius, 2014). It is suggested that this trend is being fuelled by an increasing preference among families to live in inner cities (Boterman, 2012;Boterman et al, 2010;Boterman & Karsten, 2015;Brun & Fagnani, 1994;Karsten, 2007Karsten, , 2014Lilius, 2014).…”
Section: The Family Life Course and Residential Mobilitymentioning
confidence: 99%
See 1 more Smart Citation